Characterization and numerical simulation of a new microfluidic device for studying cells-nanofibers interactions based on collagen/PET/PDMS composite - Eslam, Houra Mobaleghol; Hataminia, Fatemeh; Asadi-Saghandi, Hamid; Fayazbakhsh, Farzaneh; Tabatabaei, Nasrollah; Ghanbari, Hossein (Frontiers in Lab on a Chip Technologies, 2024)
Recently, membrane microfluidic chips (MFCs) have become available to study biological basement membranes. The nanofiber (NF) membranes are suitable substrates for cell attachment and trapping, as demonstrated by their surface properties. In this study, a novel microfluidic device based on the electrospun collagen-modified polyethylene terephthalate (PET)/polydimethylsiloxane (PDMS) was designed and fabricated to mimic biological basement membranes. Hybrid NF containing PDMS/PET and collagen were successfully fabricated by twonozzle electrospinning, and then PDMS chips were fabricated by soft lithography. The integrity of the membrane and NFs structure before (BC) and after cross-linking (AC) was evaluated by SEM, AFM, contact angle, FT-IR, BET, and tensile analysis. Cross-linking of NFs increased the diameter of NF (from 391 ± 169 nm to 660 ± 199 nm), hydrophilicity, elongation, and surface roughness (from 66.9 nm to 296.7 nm ), but decreased the pore size volume of NFs (0.06 cm3 g-1 to 0.01 cm3 g-1). Bonding of NFs was possible through the use of oxygen plasma activated materials based on PDMS and PET. After binding the NFs in the channels with oxygenated plasma, human umbilical vein endothelial cells (HUVEC) and glial cell line (C6) were successfully cultured and stained in MFC with dynamic conditions for 24 h at a flow rate of 10 µl/min. For further studies, numerical simulations were performed to evaluate the microfluidic flow in the PDMS-based device and demonstrate the fluid flow on top of a membrane. In the simulation, we use COMSOL Multiphysics to study the influence of flow rate and different surface topographies on the velocity and shear rate characteristics. The rougher microchannels exhibited a non-uniform shear rate distribution, and the flow rate was a parameter with a significant influence on the shear rate and velocity (roughness=0.3 µm). These results provide reliable evidence that the combination of electrospun NFs and cell culture can closely resemble a cell matrix.